Heat Analysis of a Vacuum Flask - Chidebe Stanley Anyanwu; Abdelrahman Gad; Hussein Bilal; Daniel Raphael Ejike Ewim (The Journal of Engineering and Exact Sciences)
Materials with low thermal conductivity like aerogel, acrylic, aluminum silicate, superfine glass wool, and phenolic foam are often used as insulation materials in engineering and have noticed increasing applications in other spheres of life, like thermal insulation in buildings and vacuum flasks. The objective of this research is to study the temperature variation of the coffee over 10 hours in a selected vacuum flask while varying the geometrical and material properties of the flask. In other words, change the parameters (without changing the fluid capacity) to minimize the heat loss over time. The range of the bottleneck radius used is from 40 mm to 60 mm, with a step size (increment) of 5 mm. The width of the whole flask is proportional to the bottleneck radius, with constant fluid capacity. The initial design used an outer and inner steel layer with plastic foam in between, and the bottleneck is made from nylon with a radius of 50 mm. This design allows the hot fluid to be at 55 oC after 10 hours in atmospheric conditions. The temperature of the coffee in the vacuum flask made of steel layers with aerogel as insulation was 72.3 oC after 10 hours, while the steel layers and CO2 insulation were 67.9 oC and the acrylic layer and aerogel were 77.89 oC after a 10-hour duration in still air. This simulation was carried out using COMSOL, and the result shows that an acrylic layer and aerogel at a bottleneck radius of 60 mm were the best combination. Verification and validation were carried out to test for convergence of the numerical and analytical solutions.